Minority Enrollment in Phase II and III Clinical Trials in Urologic Oncology. Issue 14 (10th May 2022) - Owens-Walton, Jeunice; Williams, Cheyenne; Rompré-Brodeur, Alexis; Pinto, Peter A.; Ball, Mark W.
Abstract : PURPOSE: Proportionate minority representation in clinical trials is an important step toward addressing health care inequities. Given the paucity of data on this topic in urologic oncology, we sought to quantify the enrollment of minority patients in clinical trials studying prostate, kidney, and bladder/urothelial cancers. METHODS: The ClincialTrials.gov database was queried for completed phase II and III interventional trials in prostate, kidney, and bladder cancers. The SEER database was used to calculate the US prevalence of these genitourinary cancers. Representation quotients (RQ) were calculated to describe the relative proportion of each racial/ethnic group enrolled in clinical trials over the proportion of persons from each group among national cancer cases by cancer type. RESULTS: Of 341 trials that met initial eligibility criteria, only 169 (49.7%) reported data on race or ethnicity. Aggregate RQs from 2000 to 2017 showed that White patients were continually over-represented in trials for all cancer types. Black and Asian patients were poorly represented across all cancer types. When stratified by 3-year increments, the RQs remained stable for all races, from 2000 to 2017. When stratified by ethnicity, Hispanic patients were under-represented across all cancer types in the study period. When examining representation by funding source, we found that US government–funded clinical trials proportionally enroll the most diverse patient populations over those funded by academic institutions and industry. Interestingly, more than 50% of the trials examined did not report race nor ethnicity, highlighting a crucial flaw in investigator compliance with federal clinical trial mandates. CONCLUSION: Clinical trials targeting prostate, kidney, and bladder cancers continue to under-represent racial/ethnic minority patients. On the basis of the incidence of these cancers within minority populations, efforts should focus on creating racially and ethnically inclusive cancer research.